RELIGIOUS HARMONY FORUM (FKUB) STRATEGY IN INCREASING RELIGIOUS MODERATION JURISPRUDENCE IN BENGKULU PROVINCE - Khairiah Khairiah; Irsal Irsal; Nurrahmah Putry (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2023)
Religious moderation still creates difficulties for some people; this can be seen in the emergence of intolerance, radicalism, disputes, and societal conflicts because of diversity. Therefore, a strategy for the Forum for Religious Harmony is needed to neutralize this. This research will map and describe FKUB's strategy for increasing religious moderation. Using a descriptive qualitative method, data sources were obtained from primary and secondary data from District/City and Provincial FKUB institutions. The primary data includes profiling, motivation, types of difficulties, and solutions taken by FKUB administrators and members for every difficulty they experience managing the FKUB. The results of the study can be concluded that there has been an increase in religious moderation in Bengkulu Province; it can be seen that the cooperation pattern of FKUB and the community has been implemented, has carried out work programs, has carried out coordination with religious leaders and community leaders, has carried out socialization of laws and regulations that synergize safe community life, peaceful and serene, and has carried out surveillance. However, there are still several FKUBs experiencing difficulties because they do not yet have their own secretariat office, are still in boarding status, and the facilities and infrastructure are also inadequate, so the implementation of the work program is only adjusted to the existing budget from the government, even administrators spend personal funds to continue religious moderation activities. So this paper needs to conduct further research by examining comparative aspects regionally and based on varied data and methods to resolve the difficulties of FKUB's strategy in increasing religious moderationModerasi beragama masih menimbulkan kesulitan bagi sebagian orang; Hal ini terlihat dari munculnya intoleransi, radikalisme, perselisihan, dan konflik masyarakat karena keberagaman. Oleh karena itu, diperlukan strategi Forum Kerukunan Umat Beragama untuk menetralisasi hal tersebut. Penelitian ini akan memetakan dan mendeskripsikan strategi FKUB dalam meningkatkan moderasi beragama. Dengan menggunakan metode deskriptif kualitatif, sumber data diperoleh dari data primer dan sekunder dari lembaga FKUB Kabupaten/Kota dan Provinsi. Data primer meliputi profiling, motivasi, jenis kesulitan, dan solusi yang diambil oleh pengurus dan anggota FKUB untuk setiap kesulitan yang dialami dalam mengelola FKUB. Hasil penelitian dapat disimpulkan bahwa telah terjadi peningkatan moderasi beragama di Provinsi Bengkulu; terlihat bahwa pola kerjasama FKUB dengan masyarakat telah dilaksanakan, telah menjalankan program kerja, telah melakukan koordinasi dengan tokoh agama dan tokoh masyarakat, telah melakukan sosialisasi peraturan perundang-undangan yang mensinergikan kehidupan masyarakat yang aman, tentram dan tenteram, serta telah melakukan pengawasan. Namun masih ada beberapa FKUB yang mengalami kesulitan karena belum memiliki kantor sekretariat sendiri, masih berstatus asrama, serta sarana dan prasarana juga belum memadai, sehingga pelaksanaan program kerja hanya disesuaikan dengan anggaran yang ada dari pemerintah, bahkan pengurus mengeluarkan dana pribadi untuk melanjutkan kegiatan moderasi keagamaan. Maka tulisan ini perlu melakukan penelitian lebih lanjut dengan mengkaji aspek komparatif secara regional dan berdasarkan berbagai data dan metode untuk mengatasi kesulitan strategi FKUB dalam meningkatkan moderasi beragama